Iranian nurses' knowledge and attitude toward complementary and alternative medicines: Is there any relation with quality of nursing care? - Dehghan, Mahlagha; Namjoo, Zakieh; Jafari, Mahlasadat; Kordestani, Ghazaleh; Tabebordbar, Nazanin; Payam, Fatemeh; Zakeri, Mohammad Ali; Mokhtarabadi, Sima (Frontiers in Public Health, 2022)
Background: Nurses play an important role in advising and guiding patients on effective treatments, and in this situation, it is better to be aware of complementary and alternative medicine (CAM) as well as the effects and side effects of different procedures. In addition, the quality of nursing care is directly related to the nurse's knowledge of the different treatments and preventions of different diseases and conditions. The present study aimed to investigate Iranian nurses’ knowledge and attitude towards complementary and alternative medicines (CAMs) as well as their correlation with the quality of patient care. Materials and Methods: This cross-sectional study included 267 clinical nurses from three hospitals in southern Iran. The participants were recruited using convenience sampling methods in 2020-2021. A demographic questionnaire, knowledge and attitude toward CAM questionnaires, and the Quality Patient Care Scale were used to collect data. Results: The mean score of CAM knowledge was 26.51, which was less than the questionnaire midpoint of 39. The mean score of attitudes towards CAM was 63.84, which was more than the questionnaire midpoint of 57. The mean score of the quality of patient care was 197.80, which was more than the questionnaire midpoint of 130. There was no significant correlation between knowledge about CAM, quality of patient care, and its dimensions. In addition, there was no significant correlation between attitudes towards CAM, quality of patient care, and its dimensions (P > 0.05). Conclusion: The results of the present study showed that nurses' attitudes toward the use of CAM are positive and can be a sign of their readiness to use and further integrate clinically approved CAM in patient nursing care. Due to the role of nurses in patient care and treatment, there is a need to increase nurses' knowledge of CAM, and its training should be included in the nursing curriculum. More studies are needed to identify nurses' knowledge and attitudes toward CAM and its impact on the quality of nursing care.